Twenty-four months of bacterial colonialization and infection rates in patients with transcutaneous osseointegrated prosthetic systems after lower limb amputation—A prospective analysis - Örgel, Marcus; Aschoff, Horst-Heinrich; Sedlacek, Ludwig; Graulich, Tilman; Krettek, Christian; Roth, Sabine; Ranker, Alexander (Frontiers in Microbiology, 2022)
Background After limb amputation, transcutaneous osseointegrated prosthesis systems (TOPS) are alternative rehabilitation methods to socket prosthetics. TOPS concerns two surgeries with implantation of the stem and creating the stoma through which the stem is transcutaneously guided, and the exoprosthesis can be connected. This permanently open environment connection results in constant exposure to pathogens. This study aimed to investigate the dynamics of bacterial colonization of the stoma to analyze whether obligate bacterial colonization leads to a risk of periprosthetic infections after TOPS treatment. Methods Between 2017 and 2019, this prospective study analyzed data from 66 patients aged 26 to 75 years after TOPS treatment. Microbiological swabs from the stoma concerning bacterial colonization were analyzed on the first postoperative day and three, six, 12, and 24 months after stoma creation. Infection rates and laboratory values (CRP, leukocyte count, hemoglobin), and body temperature were recorded for the above time points. Statistical analysis was performed using SPSS 28. Results The results show that a stable environment dominated by Gram-positive bacteria formed in the stoma of TOPS patients over 24 months. Staphylococcus aureus, Staphylococcus spp., and Streptococcus spp. formed the most common species. The infection rate after TOPS was 7.6% during the 24-month study period. Conclusion The stoma area's stable Gram-positive dominated bacterial taxa could be a protective factor for ascending periprosthetic infections despite a permanently open environment and bacterial colonization and explain the relatively low infection rate of 7.6%.